An explorative case study of blockchain as a means to enhancing land registry governance to uphold property and land restitution in South Africa - Tshitangano, Tom (Graduate School of Development Policy and Practice, 2025)
Land ownership is one of the fundamental constitutional rights of every citizen in South Africa. The slow progress regarding land reform and security of tenure in the form of the transfer and registration of title deeds is arguably a failure of the State to uphold the Constitution of the Republic of South Africa. Section 25 (5) of the Constitution requires the state to take measures to foster conditions which enable equitable access to land and to take reasonable legislative and other measures, within its available resources, to foster conditions which enable citizens to gain access to land on an equitable basis. Governance inefficiencies in the current land registry, specifically in relation to title deeds associated with land restitution and social housing — including acts such as corruption and fraud — hinder the progress of the constitutional requirement to reform land ownership. Such inefficiencies include the current centralisation of the Deeds Office; an incomplete land registry with a backlog of title deeds; insecure tenure for the majority of properties on communal land and in informal settlements; the inaccessibility of the land registry for the majority of the population; the high costs attached to purchasing property, accessing the land registry, conveyancing fees, deeds transfers and title deeds; processing delays caused by the current paper-based, manually driven land registry processes; and unreliable land audit reports. The Institutional Analysis and Development (IAD) framework — together with public goods, principal-agent and collective action theory — form the core elements of the conceptual framework which is evident in the registration of titles for purposes of land reform in South Africa. This framework is used to analyse the existing institutional arrangements, the factors undermining the effectiveness of the land registry, and potential governance solutions and technological safeguards. 15 15 Alongside interviews with key experts, the analysis of the available secondary empirical evidence, the legal, regulatory and grey document and media coverage, following the coding of the data and- triangulation of findings provide a detailed context for the case study and evidence base for the limited but significant role blockchain could play in enabling more effective administration and governance of the land registration, particularly at the points that it is most vulnerable to abuse and which impacts on those least able to protect their interests. From the analysis, it is proposed that the identified resource constraints and lack of institutional capacity to implement a blockchain solution could be overcome through carefully managed public-private interplays. To fulfil its primary purpose, the registry needs to be complete, accurate, secure, and accessible to anyone wishing to register title deeds. This thesis examines whether the registry does fulfil these requirements currently. The findings from a set of high-level, in-depth interviews with experts in the field reveal that, while the registry system works relatively effectively for the high-end of the market, in the lower-end of the market where most of the land and housing reform transfers take place, there is evidence of inefficiencies including, inter alia, fraud. It finds that under particular complementary conditions, blockchain could provide a decentralised and secure land registry that could transform the Deeds Office and modernise land reform and restitution to address governance inefficiencies and aberrations, particularly in relation to corruption and fraud. This thesis makes the case for blockchain technology being deployed to enable the land registry in South Africa to fulfil its functions as a public good critical to the implementation of the Electronic Deeds Registration Systems Act of 2019. In doing so, it will be able to better serve its critical role in the constitutional requirements of land restitution and housing provision. 16 16 Keywords: land registry, land reform, corruption, fraud, public good, decentralisation, technology innovation, blockchain, public-private interplays, digital transformation, effective governance